Case report: First report of Legionella pneumophila and Bordetella bronchiseptica coinfection in an immunocompromised patient - La Sorda, Marilena; Palucci, Ivana; Natalini, Daniele; Fillo, Silvia; Giordani, Francesco; Paglione, Francesco; Monte, Anella; Lista, Florigio; Mancini, Fabiola; Girolamo, Antonietta; Rota, Maria Cristina; Caporali, Maria Grazia; et al. (Frontiers in Medicine, 2024)
Legionnaires' disease (LD) is a serious type of pneumonia, typically contracted by susceptible people through the inhalation of aerosols contaminated with Legionella pneumophila (Lp). In this report, the first case of coinfection with Lp–Bordetella bronchiseptica (Bb) is described. A possible source of the Lp infection may be the hotel in Paris (France) where the patient had stayed before developing the symptoms. The Bb infection may have been transmitted by the dog with which he had constant contact, although this has not been proven.